Prevalence and Outcomes of Sudden Cardiac Arrest in a University Hospital in the Western Region, Saudi Arabia - Alzahrani, Abdullah Hussain (Saudi J Med Med Sci, 2019)
BACKGROUND: Sudden cardiac arrest (SCA) is a major cause of mortality, yet its epidemiological and outcome data in hospitals from Saudi Arabia are limited. OBJECTIVES: This study aimed to evaluate the prevalence, risk factors and outcomes of SCA in a teaching hospital in Jeddah, Saudi Arabia. METHODS: This retrospective study included all patients aged ≥18 years with SCA who were resuscitated at King Abdulaziz University Hospital, Jeddah, Saudi Arabia, between January 1 and December 31, 2016. Data were retrieved from the hospital medical records as flow sheets designed in accordance with the Utstein-style recommendations. Factors relating to mortality were analyzed using descriptive analyses and chi-square test. RESULTS: A total of 429 cases of SCA met the inclusion criteria, and its prevalence was 7.76 cases/1000 adult hospital admission. Of these, 61.3% were male, and the mean age was 58.4 years, with 36.6% aged >65 years. Only 3.5% were outside-hospital cardiac arrests. The most common initial rhythm was pulseless electrical activity/asystole (93.2%), while ventricular tachycardia/ventricular fibrillation was documented in only 29 cases (6.8%). The overall rate of return to spontaneous circulation (ROSC) was 56.2%, and 56.8% in cases of in-hospital cardiac arrest (IHCA). Patients with SCA due to sepsis had significantly increased mortality (P < 0.000; odds ratio [OR] = 0.24 [0.12–0.47 95% confidence interval [CI]]), while those with SCA due to respiratory causes had significantly better survival outcomes (P = 0.001; OR = 2.3 [1.5–3.8 95% CI]). No significant differences in outcomes were found between other risk factors, including cardiac causes. CONCLUSION: In this population, the prevalence of SCA in adults was higher than reported in many similar studies. Further, sepsis was found to affect the survival rate. Although the rate of ROSC for IHCA patients was favorable compared with other studies, it is relatively poor. This finding signifies the need to identify and control risk factors for SCA to improve survival.